2016
DOI: 10.1080/10942912.2016.1205086
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol oxidase properties, anti-urease, and anti-acetylcholinesterase activity ofDiospyros lotusL. (Plum Persimmon)

Abstract: Diospyros lotus fruit polyphenol oxidase was purified using affinity chromatography, resulting in a 15-fold enrichment in specific activity. The purified enzyme, having 16.5 kDa molecular weight on sodium dodecyl sulfatepolyacrylamide gel electrophoresis, exhibited the highest activity toward 4-methylcatechol. Maximum diphenolase activity was reached at pH 7.0 and 60°C in the presence of 4-methylcatechol. K m and V max values were calculated as 3.8 mM and 1250 U/mg protein, respectively. Ascorbic acid was a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…[34] Our results showed that the studied flavonoids had promising urease inhibition capacity showing more than 50% inhibition at a final concentration (5 mM) with an IC 50 value of ranging from 4.8 to 20.6 ( g/mL) in comparison with the positive control thiourea (5.8 g/mL) ( Table 4 and Figure 2). Urease inhibition by all flavonoids exhibited significant inhibitory activity in a concentration-dependent manner.…”
Section: Urease Inhibitionmentioning
confidence: 68%
“…[34] Our results showed that the studied flavonoids had promising urease inhibition capacity showing more than 50% inhibition at a final concentration (5 mM) with an IC 50 value of ranging from 4.8 to 20.6 ( g/mL) in comparison with the positive control thiourea (5.8 g/mL) ( Table 4 and Figure 2). Urease inhibition by all flavonoids exhibited significant inhibitory activity in a concentration-dependent manner.…”
Section: Urease Inhibitionmentioning
confidence: 68%
“…The crude enzyme extract was prepared as reported in the literature. [5,15,18,21] P. spinosa plums (30 g) were placed in a Dewar flask under liquid nitrogen for 15 min to disrupt the cell membranes, and then homogenized in a blender in 100 mL of acetate buffer (pH 7.0, 50 mM) containing 2 mM ethylenediaminetetraacetic acid (EDTA), 1 mM MgCl 2 , 1 mM phenylmethylsulphonyl fluoride (PMSF), and 6% w/v Triton X-114 for 20 min. After that, the homogenate was filtered using three layers of cheesecloth and the filtrate was centrifuged at 15,000 rpm, 4°C for 30 min.…”
Section: Preparation Of Crude Enzyme Extract and Acetone Precipitationmentioning
confidence: 99%
“…[1,2,3] Many researchers have characterized or purified PPO from various fruits and vegetables, such as Stanley plum, [4] medlar fruits, [5] mulberry fruit, [6] persimmon (Diospyros kaki L.), [3,7] mamey, [8] mango, [9] wolf's apple, [10] Yomra apple (Malus communis L.), [11] Ataulfo mango, [12] chestnut kernel, [13] Hemşin apple, [14] Pyrus elaeagnifolia, [15] Turkish Alyanak apricot (Prunus armenica L.), [16] cape gooseberry, [17] and Diospyros lotus. [18] Prunus spinosa subsp. dasyphylla, commonly known as "guvem" in Turkish, is a wild plum species of the Rosaceae family that is grown in various regions in Turkey (particularly in central, north, west, and south Anatolia) and bears a red-black-bluish, soft and edible fruit on ripening.…”
Section: Introductionmentioning
confidence: 99%
“…All kinds of residual product of plants have different biological activities and play a very important role for maintaining human health and treatment of disease [1][2][3][4][5]. So many plants were used as traditional Chinese Medicine and have many unexpected effects that western medicine cannot achieved [6][7][8]. It is well known that Diospyros lotus L. is one of the plants with specific selectivity [9].…”
Section: Introductionmentioning
confidence: 99%